2021
DOI: 10.3390/catal11060716
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Insights into the Hydrogen Evolution Reaction on the Ni3N Electrocatalyst

Abstract: Ni-based catalysts are attractive alternatives to noble metal electrocatalysts for the hydrogen evolution reaction (HER). Herein, we present a dispersion-corrected density functional theory (DFT-D3) insight into HER activity on the (111), (110), (001), and (100) surfaces of metallic nickel nitride (Ni3N). A combination of water and hydrogen adsorption was used to model the electrode interactions within the water splitting cell. Surface energies were used to characterise the stabilities of the Ni3N surfaces, al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…As shown in Figure , it is revealed that the active Ni sites of Ni 3 N@2M‐MoS 2 system (Figure 4a,b) exhibit lower energy barrier (0.653 eV) for water decomposition, compared with Ni 3 N (111) (0.73 eV) and 2M‐MoS 2 (002) (1.84 eV) reported recently. [ 37 ] Consequently, the Ni 3 N@2M‐MoS 2 composite accelerates water dissociation to provide hydrogen source with lower energy barrier for HER under alkaline media. From the microscopic view, the apparent alkaline HER activity is governed by two factors: the energy barrier of water dissociation and appropriate hydrogen adsorption/desorption.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure , it is revealed that the active Ni sites of Ni 3 N@2M‐MoS 2 system (Figure 4a,b) exhibit lower energy barrier (0.653 eV) for water decomposition, compared with Ni 3 N (111) (0.73 eV) and 2M‐MoS 2 (002) (1.84 eV) reported recently. [ 37 ] Consequently, the Ni 3 N@2M‐MoS 2 composite accelerates water dissociation to provide hydrogen source with lower energy barrier for HER under alkaline media. From the microscopic view, the apparent alkaline HER activity is governed by two factors: the energy barrier of water dissociation and appropriate hydrogen adsorption/desorption.…”
Section: Resultsmentioning
confidence: 99%
“…Nickel nitride (Ni 3 N) and its nanocomposites have demonstrated excellent application potential for water electrolysis due to its corrosion resistance, Pt-like electronic structure, and high conductivity. , However, the catalytic activity of Ni 3 N-based catalysts still needs to be further improved. As reported by Cross et al, the activation energy ( E a ) value for water splitting on the Ni 3 N (001) surface was predicted as low as 0.17 eV, indicating the fast initial water dissociation process on the Ni 3 N (001) surface . Since the water molecule can be dissociated on the Ni 3 N surface, it can be reasonably speculated that the H adsorption Gibbs free energy (Δ G H* ) would be an important indicator to evaluate the water electrolysis ability of Ni 3 N-based catalysts in alkaline media.…”
Section: Resultsmentioning
confidence: 97%
“…For example, Dzade et al studied the HER activity on the (111), (110), (001), and (100) surfaces of nickel nitride (Ni 3 N) by dispersion‐corrected DFT. [ 108 ] The calculated water adsorption energies indicate that the (111) surface shows the most favorable water adsorption. In addition, the calculated activation energies indicate that the (001) surface has the most active Volmer step for water dissociation.…”
Section: Progresses Of Representative Ni‐based Electrocatalystsmentioning
confidence: 99%